Effects of adding over-stoichiometrical Ti and substituting Fe with Mn partly on structure and hydrogen storage performances of TiFe alloy. (May 2019) - Shang, Hongwei; Zhang, Yanghuan; Li, Yaqin; Qi, Yan; Guo, Shihai; Zhao, Dongliang
Abstract: In this paper, over-stoichiometrical Ti was added into the TiFe alloy and Fe was further substituted partly by Mn for improving the hydrogen storage performances of the alloys. X-ray diffraction and scanning electron microscope results revealed that the as-cast TiFe and Ti1.1 Fe alloys contain TiFe, TiFe2 and Ti1.3 Fe phases. Adding over-stoichiometrical Ti leads to the reduction of TiFe2 and Ti1.3 Fe phases to some extent, and TiFe phase becomes the main phase for the alloy. Further substituting Fe with Mn partly causes TiFe2 phase to reduce significantly and Ti1.3 Fe phase to disappear completely. In addition, some new generated β-Ti phases also were observed in the backscatter electron images for the as-cast Ti1.1 Fe0.8 Mn0.2 alloy, which provides the initial driving force to the pulverization of the alloy powders in the hydrogen absorption process. Field emission transmission electron microscopy results show that all the alloys are nanocrystalline structure. Further substituting Fe with Mn partly makes the average grain size ( D ) decrease. It is also beneficial to the reduction of the gaseous activation condition and the improvement of the hydrogen storage capacity and kinetics, while results in a slight increase of the value of the dehydrogenation enthalpy (Δ H des ). Highlights: The as-cast TiFe, Ti1.1 Fe and Ti1.1 Fe0.8 Mn0.2 alloys are prepared. The activation temperature decreases to 423 K for the Ti1.1 Fe0.8 Mn0.2 alloy. The hydrogenation capacity is 1.764 wt.% for the Ti1.1 Fe0.8 Mn0.2 alloy. The kinetics of the Ti1.1 Fe0.8 Mn0.2 alloy is excellent. The activation mechanism for the Ti1.1 Fe0.8 Mn0.2 alloy is proposed.